Pure sensory neuropathy in patients with primary Sjögren's syndrome: clinical, immunological, and electromyographic findings. Issue 10 (October 1990) - Font, J; Valls, J; Cervera, R; Pou, A; Ingelmo, M; Graus, F
Abstract : A pure sensory neuropathy caused by lymphocytic infiltration of the dorsal root ganglia has been reported in a few patients with Sjögren's syndrome. The clinical, immunological, and electromyographic findings of five patients with this type of neuropathy and primary Sjögren's syndrome were reviewed. Typical clinical indications were the presence of a chronic asymmetrical sensory deficit, initial disease in the hands with a predominant loss of the vibratory and joint position senses, and an association with Adie's pupil syndrome or trigeminal sensory neuropathy. The simultaneous impairment of the central and peripheral evoked cortical potentials suggested that there was a lesion of the neuronal cell body. The neuropathy preceded the diagnosis of Sjögren's syndrome in four patients. Four patients were positive for Ro antibodies, but systemic vasculitis or malignancy was not found after a mean follow up of six years. These findings indicate that in patients with a sensory neuropathy the diagnosis of Sjögren's syndrome has to be considered, even if the patient denies the presence of sicca symptoms, and that appropriate tests must be carried out.